Integrative genomics identifies LMO1 as a neuroblastoma oncogene - Wang, Kai; Diskin, Sharon J.; Zhang, Haitao; Attiyeh, Edward F.; Winter, Cynthia; Hou, Cuiping; Schnepp, Robert W.; Diamond, Maura; Bosse, Kristopher; Mayes, Patrick A.; Glessner, Joseph; Kim, Cecilia; et al. (Nature (London), 2011)
GWAS identifies oncogene A genome-wide association study (GWAS) has shown that single nucleotide variants within the LMO1 locus are associated with inherited susceptibility to neuroblastoma, a childhood cancer of the sympathetic nervous system. LMO1 encodes a transcriptional regulator previously linked to cancers. Acquired structural variation in the same locus is common in patients with neuroblastoma, suggesting that loci identified through GWAS approaches might also be prone to somatic alterations that influence tumour progression. Such studies could help to identify potential therapy targets and/or biomarkers of cancer aggressiveness. Here, single nucleotide variants within the LMO1 locus are shown to be associated with inherited susceptibility to neuroblastoma, a childhood cancer of the sympathetic nervous system. Acquired structural variation in the same locus was also frequently found in neuroblastoma patients, leading to the suggestion that loci identified through genome-wide association studies might be also prone to somatic alterations and therefore identify potential therapy targets and/or biomarkers of tumour aggressiveness. Neuroblastoma is a childhood cancer of the sympathetic nervous system that accounts for approximately 10% of all paediatric oncology deaths 1 , 2 . To identify genetic risk factors for neuroblastoma, we performed a genome-wide association study (GWAS) on 2,251 patients and 6,097 control subjects of European ancestry from four case series. Here we report a significant association within LIM domain only 1 ( LMO1 ) at 11p15.4 (rs110419, combined P = 5.2 × 10 −16 , odds ratio of risk allele = 1.34 (95% confidence interval 1.25–1.44)). The signal was enriched in the subset of patients with the most aggressive form of the disease. LMO1 encodes a cysteine-rich transcriptional regulator, and its paralogues ( LMO2 , LMO3 and LMO4 ) have each been previously implicated in cancer. In parallel, we analysed genome-wide DNA copy number alterations in 701 primary tumours. We found that the LMO1 locus was aberrant in 12.4% through a duplication event, and that this event was associated with more advanced disease ( P < 0.0001) and survival ( P = 0.041). The germline single nucleotide polymorphism (SNP) risk alleles and somatic copy number gains were associated with increased LMO1 expression in neuroblastoma cell lines and primary tumours, consistent with a gain-of-function role in tumorigenesis. Short hairpin RNA (shRNA)-mediated depletion of LMO1 inhibited growth of neuroblastoma cells with high LMO1 expression, whereas forced expression of LMO1 in neuroblastoma cells with low LMO1 expression enhanced proliferation. These data show that common polymorphisms at the LMO1 locus are strongly associated with susceptibility to developing neuroblastoma, but also may influence the likelihood of further somatic alterations at this locus, leading to malignant progression.